Agricultural household modelling and family economics - Caillavet, France; Guyomard, Herve; Lifran, R. (Developments in agricultural economics, 1994)
Agricultural households, both in the European Union and world-wide, have experienced important changes during the last three decades. This book covers recent advances both in family economics and in modelling the relationship between the farm-household and the farm-firm. Both theoretical and empirical aspects of Agricultural Household Modelling and Family Economics are also discussed, providing a timely contribution to research in this area.